A Chart of the Coast of North America from the Strait of Belle Isle to Boston - Hobbs, J.S. (London: Charles Wilson late J.W. Norie & Wilson, 1848)
Relief shown by soundings and hachures. Includes descriptive notes and annotations, illustrations, and locations of fishing grounds. Insets: Halifax Harbour, Boston Harbour, St. John, the Island of St. Paul, Port St. Andrew, Liverpool Bay, St. John's, and the island of St. Pierre. Covers the area from Labrador to Boston including Newfoundland, Nova Scotia, Anticosti Island, and New Brunswick as far as Cape Cod, including the New England coastline from Connecticut to Maine. Blueback nautical chart.